2012
DOI: 10.1002/col.21788
|View full text |Cite
|
Sign up to set email alerts
|

Human brain activity and emotional responses to plant color stimuli

Abstract: This study investigated how color stimuli that consisted of green foliage plants (Epipremnum aureum) with same sized area of Kalanchoe spp. plants with four different flower colors (white, yellow, pink, and red; Kalanchoe spp.) on a dark green background influenced the brain waves and emotions of 30 undergraduate students. Electroencephalography tests were performed in order to monitor the brain‐wave responses in the prefrontal, frontal, parietal, and occipital lobes in response to the different plant color st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 17 publications
4
47
1
2
Order By: Relevance
“…High wavelength colors (e.g., yellow) are more exciting and arousing when measured with physiological measures [56]. Our findings were consistent with previous research, which showed that green plants produced more positive attitudes, and yellow may increase happiness, calmness, and restorative potential [13,57]. The relaxing effects of P. acerifolia with yellowing leaves were not as significant as G. biloba.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…High wavelength colors (e.g., yellow) are more exciting and arousing when measured with physiological measures [56]. Our findings were consistent with previous research, which showed that green plants produced more positive attitudes, and yellow may increase happiness, calmness, and restorative potential [13,57]. The relaxing effects of P. acerifolia with yellowing leaves were not as significant as G. biloba.…”
Section: Discussionsupporting
confidence: 90%
“…Behe, B. et al found that red and lavender geranium flowers were preferred over white and pink ones [11]. Green-yellow and bright green foliage developed positive feelings and calmness [12], and yellow flowered plants can be used to create pleasant places [13]. Recent attention has been paid to the role of campus landscapes in reducing stress levels of students [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…color, brightness, size, images, and shapes) often contribute to an individual's judgments. Considering a specific visual factor, a recent study has revealed that the color green has the potential to generate more positive attitudes toward the stimulus than other colors such as white, yellow, or pink (Jang, Kim, Kim, & Pak, 2014). A study by Cyr, Head, and Larios (2010) showed similar results.…”
Section: The Effects Of Wavd On Advertising Attitude and Brand Attitudementioning
confidence: 92%
“…More recently, Jang et al (2014) revealed that the human brain tends to respond more positively to stimuli with bright colors (e.g., green) rather than cool colors such as pink. In their study, Wang et al (2013) also assume that traditional advertising effects, which attitudes are part of, may not mediate the relationship between exposure to attractive images in advertising and purchase intention.…”
Section: The Effect Of Wavd On Online Purchase Intentionmentioning
confidence: 99%
“…In neurofeedback training, increasing the alpha power concomitant with the decrease in the theta power is considered an effective method of increasing cognitive performance 19) . There are also many attempts to induce alpha brainwave by auditory 20) , visual 21) , and composite stimulations 22) for relaxation or improving cognitive ability. Beta and gamma waves are known as indicators of the state of stress or data processing.…”
Section: Guess/groupmentioning
confidence: 99%